Evaluation of n-type ternary metal oxide NiMn2O4 nanomaterial for humidity sensing - Gawli, Yogesh; Badadhe, Satish S.; Basu, Aniruddha; Guin, Debanjan; Shelke, Manjusha V.; Ogale, Satishchandra (Sensors and Actuators B-Chemical, 2014)
Synthesis of mono-dispersed oleic acid (OA) capped NiMn2O4 (NMO) nanoparticles and their use for humidity sensing is reported. Oleic acid capped NMO (NMO-cOA) nanoparticles are synthesized from nickel oleate and manganese oleate complex. NiMn2O4 is obtained by removing oleic acid capping at 500 degrees C in air. X-ray diffraction analysis shows formation of pure NiMn2O4 phase which is also confirmed by HRTEM-SAED analysis. The TEM analysis also shows that the nanoparticles are nearly mono-dispersed. Doctor bladed films of NMO nanoparticles are seen to exhibit excellent humidity sensing property. The resistivity is seen to change by two orders with humidity change from 11% RH to 92% RH with fairly good linearity over the entire range. The response and recovery times are also fast. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Humidity; Impedance; Nanoparticles; NiMn2O4; Oleic acid; Sensor